Numerical modelling of the flow around the tanker hull at model scale - Bućan, Boris, inženjer strojarstva (Array, 2008)
Principles of RANSE-based (Reynolds Averaged Navier-Stokes Equations) numerical modelling of a fl ow around the tanker model hull are introduced with the application of the CD-adapco STAR-CCM+ (Computational Continuum Mechanics) software package in the fi eld of ship hydrodynamics. The numerical model used in simulation is drawn up through base parameters and methods of geometrical and mathematical modelling. Results of two numerical simulations performed at design and ballast loading conditions are presented and a comparison with available experimental data is made. Some aspects of further improvements of the presented numerical model are pointed out